Crosstalk between wire pairs above a composite ground plane - Lansink Rotgerink, J.H.G.J.; Happ, F.; Es, J.J.P. van (IEEE, 2016)
Crosstalk between two wire pairs in three different configurations is compared to investigate the influence of replacing aluminium by carbon-fibre-reinforced plastic composite material in ground returns. Measurements and simulations show the same interesting effect involving a transition frequency at which the influence of the composite ground plane changes. For low frequencies it acts as a transparent layer on crosstalk behaviour, whereas for higher frequencies it can significantly decrease crosstalk levels. This phenomenon can be explained physically by investigating the skin effect of the composite ground plane. Reverse engineering can even lead to an estimation of the conductivity of the composite material when a crosstalk measurement is at hand.